Case studies in Islamic economics and finance Workshop on Islamic Economics and Finance (WIEF 2011), 6-7 December 2011, Danau Golf Club, UKM - Workshop in Islamic Economics and Finance (2011 : Bangi, Selangor).; Shahida Shahimi; Noreha Halid; Abdul Ghafar Ismail; Wan Norsyakila Wan Kamarudin; Universiti Kebangsaan Malaysia. Fakulti Ekonomi dan Pengurusan (Bangi : Fakulti Ekonomi dan Pengurusan, Universiti Kebangsaan Malaysia, 2011)
Contains 37 papers presented in Workshop in Islamic economics and finance 2011.
Title from first page on document.
System requirements: Adobe Acrobat Reader.
Keywords: Finance -- Islamic countries -- Congresses; Finance -- Religious aspects -- Islam -- Congresses; Banks and banking -- Religious aspects -- Islam -- Congresses